Retrospective analysis of GnRH-a prolonged protocol for in vitro fertilization in 18,272 cycles in China - Lifeng Tian; Leizhen Xia; Qiongfang Wu (BMC, 2022)
Abstract Background This large-cohort, retrospective study investigates the relationship between the number of oocytes retrieved and the clinical outcomes for patients receiving the GnRH-a prolonged protocol (mGnRH-a protocol) for fertilization in vitro or intracytoplasmic sperm injection-embryo transfer (IVF/ICSI-ET) treatment. Results We categorized 18,272 cycles into three groups by the number of oocytes retrieved (1-8, 9-17, and ≥ 18) during IVF with the GnRH-a prolonged protocol at the Reproductive Medical Center of Jiangxi Maternal and Child Health Hospital from January 2014 to December 2018 (excluding oocyte donation cycles), analyzing the associations among oocyte number and live birth rates (LBRs) or cumulative LBRs (CLBRs), as well as the rate of moderate-to-severe ovarian hyperstimulation syndrome (OHSS). We defined the primary outcome as LBR and the secondary outcome to include the rate of patients at high risk for OHSS. The LBR (with fresh ET) per cycle of oocyte pick-up increased as the number of retrieved oocytes increased from 1 to ~ 8, plateaued between 9 ~ 17, and steadily decreased thereafter. However, the CLBR per cycle continued to increase as the oocyte number increased, as did the incidence of moderate-to-severe OHSS. Conclusions Our results show a strong relationship between the number of oocytes retrieved and the CLBR following IVF treatment. The balance between treatment success and the risk of complications, especially OHSS, should be investigated further. We recommend a fresh-ET strategy for the GnRH-a prolonged protocol because the endometrial receptivity in the fresh cycles was better than those in the frozen cycles.